Germanium Nanosheets with Dirac Characteristics as a Saturable Absorber for Ultrafast Pulse Generation (Adv. Mater. 32/2021). Issue 32 (12th August 2021) - Mu, Haoran; Liu, Yani; Bongu, Sudhakara Reddy; Bao, Xiaozhi; Li, Lei; Xiao, Si; Zhuang, Jincheng; Liu, Chen; Huang, Yamin; Dong, Yemin; Helmerson, Kristian; Wang, Jiaou; et al.
Abstract : Germanene Several layers of germanene with Dirac characteristics and ultrafast carrier dynamics are produced by Guanyu Liu, Yi Du, Qiaoliang Bao, and co‐workers, as reported in article number 2101042 . As a new group‐IV member material, germanene is further demonstrated as a promising saturable absorber to construct ultrafast mode‐locked lasers and generate sub‐picosecond pulses in the telecommunication band.